Multi-Ligament Reconstruction in an Adolescent Female Affected by Congenital Femoral Deficiency and Complete Anterior and Posterior Cruciate Ligament agenesis: A Case Report - Simone Giusti; Maria Beatrice Bocchi; Edoardo De Fenu; Osvaldo Palmacci; Ezio Adriani (Clinics and Practice)
Purpose: Multi-ligament reconstruction in adolescent patients affected by congenital femoral deficiency is an extremely rare and delicate surgical procedure. There are very few reported cases of complete anterior and posterior cruciate ligament agenesis in these patients. Methods: We present a complex case of a 16-year-old girl affected by congenital femoral deficiency and ipsilateral tibial hypoplasia who was treated successfully for a complete agenesis of the anterior (ACL) and posterior (PCL) cruciate ligament with single-sitting ACL and PCL reconstruction. Results: The adolescent patient was successfully reconstructed with excellent clinical results. Conclusions: Knee MRI (Magnetic Resonance Imaging) should be requested in all patients affected by congenital femoral deficiency to exclude ligamentous agenesis. Where present, these should be reconstructed at an early stage as soon as limb-lengthening procedures are completed. If still skeletally immature, physeal-sparing surgical techniques should be implemented.